Primitive neuroectodermal tumor presenting as a presacral mass: A rare case report with review of literature - Pradnya S Bhadarge; Sonali S Datar; Pradeep S Umap; Alok C Shrivastava (Wolters Kluwer Medknow Publications, 2017)
Primitive neuroectodermal tumors (PNETs) are a group of highly malignant small round cell tumor (SRCT) of neuroectodermal origin. They exhibit a great diversity in their clinical manifestations and pathologic similarities with other SRCTs. PNET commonly occurs in the central nervous system, head and neck region, paravertebral region, pelvis, and lower extremities. PNET presenting as a presacral mass is very rare. We present a case of 65-year-old female patient presented with a mass in the abdomen. Exploratory laparotomy with excision of mass was carried out. Histopathology revealed the diagnosis of PNET. The rarity of PNET at presacral region prompted the description of this case.